NUTRITION AS POSSIBLE ETHIOLOGICAL AGENT OF WINTER DISEASE SYNDROME IN SEA BREAM (Sparus aurata L.) - Gordana Šarušić; Lav Bavčević (Croatian Journal of Fisheries, 2000)
The circumstance of winter disease phenomenon in intensively reared sea bream (Sparus aurata L.) has been described. It’s occurence in Mediterranean has been registered and reported by several authors. The aim of this paper is to contribute to the comprehension on the aethiology of this syndrome which is causing significant losses in one year old cultured fish. Different types of commercial diets were introduced during 1994/95 rearing season to the sea bream reared in floating cages. The feeds were displaying differences in energetic compound level and vitamin A, D3 and E content. Health difficulties and mortality in the observed fish groups at the beginning of the problem, did not indicate any biotic agent as being responsible for such condition. Clinical features and mortality in the groups affected by winter disease syndrome were increasing by low sea temperature and correlating with feeding period by food containing low levels of protein, lipids and vitamins. Pathological findings were in particularly related to the organs involved in digestion. Growth rate was characteristic for the group that were suffering winter disease, where increasing in length was not followed by body weight. Clinical signs, simptomathology related to the organs involved in digestion, liver histology analyses, weight losses and pattern of weight and length relation, correlation between used feeds and occurrence of winter disease, implicated nutrition as one of most possible ethiological agent of this condition. Nutritional interventions applied contributed in comprehension of the winter disease syndrome. The relationship between nutritional requirements, particularly regerding autumn-winter period, has been researched and analyzed. The results approved our basic hypothesis.